2018
DOI: 10.1017/s0958344017000325
|View full text |Cite
|
Sign up to set email alerts
|

Orientations to negotiated language and task rules in online L2 interaction

Abstract: Recent research shows that negotiation of meaning in online task-oriented interactions can be a catalyst for L2 (second/foreign/additional language) development. However, how learners undertake such negotiation work and what kind of an impact it has on interactional development in an L2 are still largely unknown mainly due to a lack of focus on task engagement processes. A conversation analytic investigation into negotiation of meaning (NoM) in task-oriented interactions can bring evidence to such development,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 65 publications
2
33
0
1
Order By: Relevance
“…Interestingly, language policing practices may be self-initiated, where a speaker will self-correct the choice of language, or other-initiated, as participants may hold each other accountable for violating the language policy (cf. embedded and implicit language policing in Hazel, 2015; rule and language policing in Sert & Balaman, 2018). Reporting from a complementary Chinese classroom in the U.K., Wei and Wu (2009) have found that the students challenge the teacher's traditional authority as well as the monolingual norm.…”
Section: Language Alternation and Policy In Educationmentioning
confidence: 99%
“…Interestingly, language policing practices may be self-initiated, where a speaker will self-correct the choice of language, or other-initiated, as participants may hold each other accountable for violating the language policy (cf. embedded and implicit language policing in Hazel, 2015; rule and language policing in Sert & Balaman, 2018). Reporting from a complementary Chinese classroom in the U.K., Wei and Wu (2009) have found that the students challenge the teacher's traditional authority as well as the monolingual norm.…”
Section: Language Alternation and Policy In Educationmentioning
confidence: 99%
“…Starting from the notion that development means change over time, most studies use a longitudinal research design that follows the interactional practices of one or a small number of target participants over a longer or shorter time span (days, months, or years). These studies often focus on a defined social action or activity, such as the opening of a task or a storytelling (Hellermann, , ; Pekarek Doehler & Berger, ), self‐repair (Hellermann, ; Sert & Balaman, ), or practices for managing transitions between topics and activities (Kim, ; Nguyen, ; Nguyen, ). Based on longitudinal recordings of naturally occurring conversations and related micro‐level transcriptions, they track how the target participants change their practices for accomplishing the particular actions or activities over time.…”
Section: Methodological Issues In Studying the Development Of L2 Icmentioning
confidence: 99%
“…Already during this introduction, both Parina and Amalie share that they have seen the researcher, Parina in Danish (line 02), and Amalie in English (line 04), demonstrating her ability to communicate in English outside of regular classroom interaction (despite the non-standard grammatical form used). By not only saying that she has seen the researcher already, but also translating or recycling Parina's previous comment, Amalie is positioning herself as a 'translator' of the other children, and maybe even policing Parina's language choice (Amir & Musk, 2013;Balaman, 2016;Sert & Balaman, 2018). After the researcher states that she is filming (line 06), Amalie engages in a content-oriented parallel activity (Koole, 2007) as she turns to Frederikke and whispers "she is filming us" to her (line 10).…”
Section: Category-bound Obligations Of Strong Studentsmentioning
confidence: 99%